Percepción ambiental, análisis comparativo de la población en los Asentamientos Humanos 31 de mayo y don Mario (shushuna), carretera Zungaro Cocha, 2023 - Ramirez Vela, Miriam del Fatima (2023)
The present reserch was carried out in the 31 de Mayo and Don Mario (Shushuna) Human villages located on the Zungarococha highway. The study is located in the district of San Juan Bautista, province of Maynas, Loreto region. The objective of the research was to analyze the environmental perception that families in the study area located on the Zungarococha highway have regarding the environmental problems proposed by the report by Ernesto Raes Luna and Marc Dourojeanni, 2016 regarding their environment within which There are three most relevant and perceived environmental problems such as native peoples, collective territories, land concessions and titling, socially and environmentally irresponsible sectoral planning, deforestation, illegal logging and poor forest management. Likewise, it is evident that there is a breach of policy axis 3, point 3. Social inclusion in the environmental management of the National Environmental Policy, since the families of the study area do not know about the environmental information that should be promoted by the authorities and is the reason why they are not subject to active citizen participation as a means of inclusion within urban distribution plans and environmental management, being considered as rural communities due to their population status. Regarding opportunities for improvement, the families identified the needs that they would have in their rural communities in order to contribute to the improvement of administration and environmental management, and on the transformative action that would fully benefit the conditions in which they are currently found and in turn participate actively with environmental improvement in general.